2023
DOI: 10.3390/su15021089
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Short Supply Chains in the Agri-Food Sector

Abstract: Short supply chains have recently gained increased attention because of the turbulence in the global environment caused by exogenous influences that create unstable and uncertain conditions. The emergence of short supply chains is of particular importance for sustainable development at large, but also for the viability of vulnerable communities and areas (e.g., remote and isolated, and islands). This paper aims to explore the area of short supply chains focusing on the agri-food sector from a bibliometric stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…If this is attained, they will be of much value as much as developed nations. Citation analysis revealed those papers, authors, journals, institutions and countries all are found to form clusters with wide range of existing opportunities for new researchers and prospective authors, whether to join existing research trend or to form new research area in Thermal and Non-thermal Pasteurization (TNP) of citrus fruits in the domain of food processing [ 55 ]. corroborate our observation relative to citation within countries and among countries.…”
Section: Discussionmentioning
confidence: 99%
“…If this is attained, they will be of much value as much as developed nations. Citation analysis revealed those papers, authors, journals, institutions and countries all are found to form clusters with wide range of existing opportunities for new researchers and prospective authors, whether to join existing research trend or to form new research area in Thermal and Non-thermal Pasteurization (TNP) of citrus fruits in the domain of food processing [ 55 ]. corroborate our observation relative to citation within countries and among countries.…”
Section: Discussionmentioning
confidence: 99%
“…The data were saved as plain text records, and their contents were selected as full records and cited references. Excel was used to create relevant tables and VOSviewer 1.6.20 was used to visualize the hotspots of countries, institutions and keywords [16][17][18][19].…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…Lately, alternative food networks such as short agri-food supply chains (SAFSCs), have gained increased attention [56,57]. Because farmers/producers and consumers engage directly with SAFSCs, trust is a critical component.…”
Section: Insights From Trust In the Agri-food Sectormentioning
confidence: 99%